Perlindungan Hukum Terhadap Tenaga Kesehatan Dan Gugus Tugas Percepatan Covid-19 Di Puskesmas - Conita Aulia Wijayanti (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
At the beginning of 2020 the world was shocked by a new virus thought to have originated from Wuhan, China. named 2019 Novel Corona virus. The World Health Organization (WHO) names the new virus as corona virus disease 2019 (Covid-19), that health workers, both doctors, nurses and hospital administration staff, need legal protection from the government. Health workers are willing to devote themselves to serving public health and even sacrifice their lives and those of their families to tackle the spread of Covid-19. The formulation of the problem in this study is How is legal protection for health workers and the Covid-19 acceleration task force? and How is the form of guidance and supervision of the implementation of Covid-19 prevention services, the method used is a normative juridical approach. The work safety of health workers due to the Covid-19 pandemic has not been carried out properly as mandated in laws and regulations, in the implementation of the rights of health workers During the Covid-19 pandemic, it is still neglected and has not been fulfilled. Therefore, the role and responsibility of the government is needed to fulfill the rights of health workers as the frontline.